Proceedings of the 2020 Conference on Empirical Methods in Natural Language Processing (EMNLP) 2020
DOI: 10.18653/v1/2020.emnlp-main.466
|View full text |Cite
|
Sign up to set email alerts
|

AmbigQA: Answering Ambiguous Open-domain Questions

Abstract: Ambiguity is inherent to open-domain question answering; especially when exploring new topics, it can be difficult to ask questions that have a single, unambiguous answer. In this paper, we introduce AMBIGQA, a new open-domain question answering task which involves finding every plausible answer, and then rewriting the question for each one to resolve the ambiguity. To study this task, we construct AMBIGNQ, a dataset covering 14,042 questions from NQ-OPEN, an existing opendomain QA benchmark. We find that over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 23 publications
(22 reference statements)
2
55
0
Order By: Relevance
“…We observed there are many ambiguous questions included in NQ data. Consistent with the findings of Min et al (2020), we have found that many of the ambiguous questions or illposed questions can be fixed by small edits, and we suggest asking annotators to edit those questions or asking them a follow-up clarification instead of simply marking and leaving the questions as is in the future information-seeking QA dataset creation.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We observed there are many ambiguous questions included in NQ data. Consistent with the findings of Min et al (2020), we have found that many of the ambiguous questions or illposed questions can be fixed by small edits, and we suggest asking annotators to edit those questions or asking them a follow-up clarification instead of simply marking and leaving the questions as is in the future information-seeking QA dataset creation.…”
Section: Discussionsupporting
confidence: 86%
“…While all the individual pieces might be revealed in independent studies (Min et al, 2020;Oguz et al, 2020), our study quantifies how much each factor accounts for reducing answer coverage.…”
Section: Discussionmentioning
confidence: 89%
“…Question Rewriting QR has been studied for augmenting training data (Buck et al, 2018;Sun et al, 2018;Zhu et al, 2019; or clarifying ambiguous questions (Min et al, 2020). In CQA, QR can be viewed as a task of simplifying difficult questions that include anaphora and ellipsis in a conversation.…”
Section: Related Workmentioning
confidence: 99%
“…To ensure that our datasets properly "isolate the property that motivated [the dataset] in the first place" (Zaenen, 2006), we need to explicitly appreciate the unavoidable ambiguity instead of silently glossing over it. 14 This is already an active area of research, with conversational QA being a new setting actively explored by several datasets (Reddy et al, 2018;Choi et al, 2018); and other work explicitly focusing on identifying useful clarification questions (Rao and Daumé III), thematically linked questions (Elgohary et al, 2018) or resolving ambiguities that arise from coreference or pragmatic constraints by rewriting underspecified question strings (Elgohary et al, 2019;Min et al, 2020).…”
Section: A Call To Actionmentioning
confidence: 99%